Development of Teaching E-Modules on Atomic Structure Material Based on the Merdeka Curriculum - Melviani; Eny Enawaty; Masriani (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The purpose of this study was to develop and test the feasibility of materials and media, as well as to observe teachers' responses to e-learning modules on atomic structure based on the independent curriculum. This study uses the Research and Development method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. However, the development process is limited to the development stage with the aim of producing e-learning modules that are theoretically feasible based on expert assessment and user response, without empirically testing the effectiveness of the product. The module that has been developed is tested for feasibility by each of the 2 media experts and material experts to determine whether the module is suitable for use. In addition to the feasibility assessment, a response test to the product was also carried out involving 2 teachers from driving schools in Pontianak city. The results of the analysis in the material test were 88%, the media test was 84%, and the teacher response questionnaire to the teaching module was 96%. So it can be concluded that the teaching e-module on atomic structure material based on the independent curriculum developed is feasible to use as a learning tool because it has passed the feasibility assessment by material and media experts and received a very good response from chemistry learning teachers because it has passed the response test. The uniqueness of this research lies in the development of an e-learning module that systematically maps Learning Outcomes (CP) into Learning Objectives (TP) and Learning Objective Sequences (ATP), and is designed in an interactive digital format to overcome teachers' difficulties in planning lessons under the Merdeka Curriculum. Researchers suggest continuing this research at the next stage, namely implementation and evaluation to see the effectiveness of the teaching modules produced because the teaching modules can also be used by teachers in learning chemistry so as to make it easier for teachers to have teaching module references that are more flexible and can be accessed at any time.